Physical chemistry a very short introduction - Atkins, P. W. (Peter, William) 1940- (Very short introductions, 2014)
"With the development of a variety of exciting new areas of research involving computational chemistry, nano- and smart materials, and applications of the recently discovered graphene, there can be no doubt that physical chemistry is a vitally important field. It is also perceived as the most daunting branch of chemistry, being necessarily grounded in physics and mathematics and drawing as it does on quantum mechanics, thermodynamics, and statistical thermodynamics. With his typical clarity and hardly a formula in sight, Peter Atkins' Very Short Introduction explores the contributions physical chemistry has made to all branches of chemistry. Providing insight into its central concepts Atkins reveals the cultural contributions physical chemistry has made to our understanding of the natural world."--Publisher's description.